REPRODUCTIVE HEALTH OF CHILDREN AND TEENAGERS UNDERWENT SURGICAL CORRECTION ASSOCIATED WITH ANDROLOGIC PATHOLOGY - S.P. Yatsyk (Pediatričeskaâ Farmakologiâ, 2009)
The article outlines diagnostic methods of fertile function disturbance among teenagers underwent surgical intervention on genitalia. It emphasizes the necessity to observe this group of patients and establish risk groups according to a possible disturbance of fertile function during their adult life period. Key words: varicocele, inhibin type B, anti-sperm antibodies, follicle-stimulating hormone.